Rock-a-bye Bible : selected scripture from the Authorized King James Version with favorite rhymes from the Christian Mother Goose books - Decker, Marjorie Ainsborough (Iowa Falls, Iowa : World Bible Publishers, 1987)
A collection of nursery rhymes and tales written to emphasize Christian principles.
At head of title: Christian Mother Goose.
Keywords: Christian life; American poetry; Nursery rhymes; Christian life -- Poetry; Nursery rhymes -- Adaptations